ON g, g*, g**-COMPACT FUNCTIONS - Ali, Haider J; Mohammed, Arkan J (Al-Nahrain Journal of Science, 2010)
In this paper we introduce and study g , g* , g* *- compact functions and we study the relation ofcompact functions with this types of the functions. Finally, we study further theorems andproperties on g , g* , g* *- compact functions